(untitled) (Research, Society and Development, 2020)
The microbiological safety of water is related to faecal contamination, and conventional biomarkers of water contamination for human consumption do not allow revealing what the source of faecal contamination is. The aim of the research is to find scientific evidence about alternative biomarkers that can identify the source of faecal contamination in water for human consumption. This is a qualitative and descriptive research, an integrative literature review. Biomarkers used were bacteria, viruses, protozoa and archaea, and 72.7% of the studies had samples from groundwater. Detection rates of Bacteriodales genetic markers specific to humans were higher than on animals in most studies, which were performed in groundwater. Archeal markers were more prevalent than Bacteriodales in the studied water bodies. The seasonal variability in the occurrence of fecal contamination biomarkers was identified in 60% of the studies that carried out this assessment. The sensitivity and specificity of species-specific markers may vary according to the region studied. It is suggested that the use of these markers should be combined with the monitoring of conventional fecal contamination biomarkers. It is perceived the need for further studies on the use of biomarkers to identify possible sources of human and / or animal contamination in water for human consumption, and the assess the risk and incidence of waterborne diseases in the studied places.